Modelling And Analysis Of The Dynamic Behavior Of Power System During Large-Scale Contingency - Abdulraheem, Bashar Sabeeh (2016)
The main variables that ensure the power system stability of any electrical network are system frequency and voltage profile. To provide sufficient power, it is necessary to extend the electrical power network by adding either new generating units or transmission lines. Due to economic and environmental constraints for new installation, and consequent growth of loads that create overload situation due to extremely loaded network or increased transmission lines flow on existing transmission lines, power system stability has become more susceptible to various disturbances and outages. This dissertation presents investigation on the dynamic behavior of power system in terms of system frequency and voltage profile during extreme contingencies such as loss of single generator units, extremely loaded network, loss of a single transmission line, and occurring island grids. This paper also presents investigation on system frequency sensitivity for various severity levels (light, medium, and heavy) of these contingencies and implemention of load shedding scheme at predetermined frequency in order to restore the system frequency and voltage profile within acceptable limits. IEEE 39 bus has been modeled as a test case by using DigSILENT power factory software, and the results has been validated with IEEE reference case. The test case has been used to perform the contingencies events. To evaluate the impact of these contingency events on transmission system in terms of system frequency and voltage profile, the system behavior has been observed before and after implementing load shedding scheme. The results show that a deficit in power system due to loss of generator unit having larger capacity will cause severe drop in system frequency and voltage profile. Meanwhile, increasing load demand with insufficient generation within specific electrical network will create overload situation, leading to decline system frequency and voltage profile. The severity of decline increases with the increase of the severity of overload. The results for loss of a single transmission line show minor change in system frequency and voltage. In addition, the critical branches based on generator has been identified in IEEE 39 bus system, and the results show that loss of these critical branches causes the system to behave exactly similar to loss of a single generator unit in terms of system frequency and voltage. The results also show that creating island grid with large amount of exchange power with neighbouring zones also causes severe decline in system frequency and voltage. System behavior has been observed after implementing load shedding scheme for above contingencies events, and the results show improvement in system frequency and voltage behavior within acceptable limits and has regained power system stability. This research study provides an insight into the need of delicate balance between electricity generation and load demand, and the consequences of rapid disturbances in electrical power system.